DELAYED PROMOTION AS A PREDICTOR OF JOB STRESS AMONG SECONDARY SCHOOL TEACHERS IN ENUGU STATE, NIGERIA - Onah, Joseph (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Promotion is a ubiquitous component in Nigeria's civil service. However, the teaching profession in the country, especially at the state level, is usually characterized by irregular promotions. The study examined the effect of delayed promotion on job stress among secondary school teachers in Enugu state. One hundred and thirty-three teachers pooled from the post-primary school system in Enugu state, Nigeria, completed the self-report instrument used for data collection. A cross-sectional research design was adopted in the study. Data were computed using a simple linear regression model. The analysis revealed a positive interaction between delayed promotion and job stress, F (1,131) = 32.61, p < 0.05. The finding indicated that delayed promotion contributed to about 13.1% of teachers' job stress variation. The finding has implications for teachers' well-being and quality academic-related output.